Ποικιλιακή σύνθεση εσπεριδοειδών στην Κύπρο - Αριστείδης, Σταύρος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Citrus fruits are one of the most important crops worldwide, both in production as in marketability and economic value, with total world production of over 120 million tonnes. Since ancient times, Cyprus has grown and marketed citrus fruits, rendering it one of the most important horticultural crop of the island today. Unfortunately, the situation has changed considerably in recent decades, after large areas of citrus have been grubbed up and production has decreased dramatically. Nevertheless, due to the favorable climate of the island and the know-how that exists, their cultivation continues incessantly and with the prospect of being there. In Cyprus, four different types of citrus are grown, with each having its own distinct varieties. These species are oranges with production 34%, mandarins with production 40%, lemons 12% of production and grapefruits 14% of production. In addition, remarkable mention can also be made to the mandarins “Mandora” which was successfully grown on the island in the previous years, but there are now tendencies to eradicate it, mainly due to the promotion of new varieties. In the next section, I dealt with 5 new promising citrus varieties (Orri, M7, Kinnow LS, US Furr-ST, Tango), which have recently been marketed and constitute improved varieties with desirable characteristics for the consumer. The “Valencia” orange is one of the major varieties cultivated worldwide, which is also cultivated in Cyprus. In the present study, we studied the titratable acidity (TA) by using automatic titrator, total soluble solids (TSS) with sugar refractometer and the juice content from 250 different Valencia fruits, which were harvested from 10 different pieces on the citrus farm in the Fasouri area. Results showed rates of juice content between 45-50%, TSS 12-13%, titratable acidity 1.4-1.7% and maturity index between 7 and 8.
Keywords: Citrus; Valencia; Acidity; Juice content; Soluble solids; Εσπεριδοειδή; Valencia; Οξύτητα; Χυμοπεριεκτικότητα; Διαλυτά στερεά συστατικά